Bioinspired sandwich-like hybrid surface functionalized scaffold capable of regulating osteogenesis, angiogenesis, and osteoclastogenesis for robust bone regeneration. (15th December 2022) - Wu, Minhao; Chen, Feixiang; Liu, Huifan; Wu, Ping; Yang, Zhiqiang; Zhang, Zhe; Su, Jiajia; Cai, Lin; Zhang, Yufeng
Abstract: Recently, strategies that focus on biofunctionalized implant surfaces to enhance bone defect healing through the synergistic regulation of osteogenesis, angiogenesis, and osteoclastogenesis have attracted increasing attention in the bone tissue engineering field. Studies have shown that the Wnt/β-catenin signaling pathway has an imperative effect of promoting osteogenesis and angiogenesis while reducing osteoclastogenesis. However, how to prepare biofunctionalized bone implants with balanced osteogenesis, angiogenesis, and osteoclastogenesis by activating the Wnt/β-catenin pathway has seldom been investigated. Herein, through a bioinspired dopamine chemistry and self-assembly method, BML-284 (BML), a potent and highly selective Wnt signaling activator, was loaded on a mussel-inspired polydopamine (PDA) layer that had been immobilized on the porous beta-tricalcium calcium phosphate (β-TCP) scaffold surface and subsequently modified by a biocompatible carboxymethyl chitosan hydrogel to form a sandwich-like hybrid surface. β-TCP provides a biomimetic three-dimensional porous microenvironment similar to that of natural cancellous bone, and the BML-loaded sandwich-like hybrid surface endows the scaffold with multifunctional properties for potential application in bone regeneration. The results show that the sustained release of BML from the sandwich-like hybrid surface significantly facilitates the adhesion, migration, proliferation, spreading, and osteogenic differentiation of MC3T3-E1 cells as well as the angiogenic activity of human umbilical vein endothelial cells. In addition to osteogenesis and angiogenesis, the hybrid surface also exerts critical roles in suppressing osteoclastic activity. Remarkably, in a critical-sized cranial defect model, the biofunctionalized β-TCP scaffold could potentially trigger a chain of biological events: stimulating the polarization of M2 macrophages, recruiting endogenous stem cells and endothelial cells at the injury site to enable a favorable microenvironment for greatly accelerating bone ingrowth and angiogenesis while compromising osteoclastogenesis, thereby promoting bone healing. Therefore, these surface-biofunctionalized β-TCP implants, which regulate the synergies of osteogenesis, angiogenesis, and anti-osteoclastogenesis, indicate strong potential for clinical application as advanced orthopedic implants. Graphical abstract: Image 1